2004
DOI: 10.1158/0008-5472.can-04-1905
|View full text |Cite
|
Sign up to set email alerts
|

Gefitinib Induces Apoptosis in the EGFRL858R Non–Small-Cell Lung Cancer Cell Line H3255

Abstract: Somatic mutations in the tyrosine kinase domain of the epidermal growth factor receptor (EGFR) have recently been described in patients with non-small-cell lung cancer (NSCLC) who achieve radiographic regressions to the EGFR inhibitor gefitinib. One of these mutations, L858R (Leu3 Arg), is also found in NSCLC cell line H3255, which is very sensitive to gefitinib treatment. We characterized nine NSCLC cell lines (three isolated from patients with bronchioloalveolar carcinoma and six isolated from patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

32
253
2
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 331 publications
(291 citation statements)
references
References 19 publications
32
253
2
4
Order By: Relevance
“…Our calculated responses for ERK and Akt signaling for normal EGFR expression agree with the qualitative experimental observations of Sordella et al 61 and Tracy et al: 65 namely, that the ERk stimulation levels decrease and the Akt levels are maintained for the mutant cells with normal EGFR expression levels. This preferential activation of Akt in L834R mutant cell lines observed in these experiments is consistent with the systems level predictions from our simulations.…”
Section: Discussionsupporting
confidence: 88%
“…Our calculated responses for ERK and Akt signaling for normal EGFR expression agree with the qualitative experimental observations of Sordella et al 61 and Tracy et al: 65 namely, that the ERk stimulation levels decrease and the Akt levels are maintained for the mutant cells with normal EGFR expression levels. This preferential activation of Akt in L834R mutant cell lines observed in these experiments is consistent with the systems level predictions from our simulations.…”
Section: Discussionsupporting
confidence: 88%
“…These experiments revealed that, in H441 cells, the dominant RTK activity was for EGFR, Her2, Her3 and Met receptors. The H441 cell line has been previously shown to be resistant to gefitinib and cetuximab (Tracy et al, 2004;Mukohara et al, 2005). We found that the activity of EGFR in these cells can be inhibited by the dual EGFR and Her2 kinase inhibitor GW2974 at high micromolar concentrations, which also affects the phosphorylation of Stat3, Akt and Shc, but not Erk1/2.…”
Section: Discussionmentioning
confidence: 81%
“…The NSCLC cell lines A549, NCI-H1395, NCI-H1650, NCI-H1666, NCI-H1781, NCI-1975, NCI-H23, NCI-H2126, NCI-H441, NCI-H820, HCC2935, HCC4006, and HCC827 were purchased from ATCC (Manassas, VA, USA). H3255, H3255GR, HCC2279, and PC-9 have been previously described (Ono et al, 2004;Tracy et al, 2004;Engelman et al, 2006). Ma1, and Ma70 are NSCLC cell lines harbouring EGFR mutations that were established at the Kinki University, Osaka, Japan.…”
mentioning
confidence: 99%